Diisooctyl phthalate (DIOP) exposure leads to cell apoptosis to HUVEC cells and toxicity to Caenorhabditis elegans through increasing the oxidative stress - Siyuan Luo; Junnan Li; Yuqing Zhou; Zihang Zhai; Qiang Li; Zhenglin Huang; Wencan He; Kejun Zhong; Bo Kong; Zanxian Xia; Hang Fai Kwok; Lipeng Zhu (Ecotoxicology and Environmental Safety)
Diisooctyl phthalate (DIOP), a common phthalate plasticizer, is frequently encountered in everyday life. Despite its widespread use, there is a dearth of toxicological research on DIOP, resulting in incomplete knowledge of its potential harmful effects. Our current research endeavored to provide a comprehensive evaluation of DIOP's toxicological profile using both cellular and Caenorhabditis elegans models as our in vitro and in vivo study subjects. Our results demonstrate that DIOP markedly decreases the viability and colony-forming ability of HUVECs. Moreover, this cytotoxicity correlates with elevated levels of reactive oxygen species (ROS), causing cell cycle arrest at the G1 phase and the induction of cell apoptosis. In addition, DIOP adversely affects the growth, movement, and reproductive fitness of C. elegans, as well as other physiological aspects such as body curvature, egg-laying capability, and body length. C. elegans exposed to DIOP exhibit increased oxidative stress, evidenced by higher ROS levels and lipofuscin buildup. Importantly, the PI3K/AKT and MAPK pathways are implicated in the response to DIOP-induced toxicity. This study, therefore, highlights the potential toxicity of DIOP in both cellular and organismal models, advancing our understanding of the detrimental effects associated with exposure to DIOP.